Antiplatelet Aggregation, Cardiotonic, Anti-Inflammatory, Antioxidant, and Calcium Channel Antagonistic Potentials of Nepeta ruderalis Buch. (1st June 2020) - Aleem, Ambreen; Janbaz, Khalid Hussain; Imran, Imran; Wahid, Muqeet; Bibi, Sumbal; Afzal, Khurram; Asad, Muhammad Hassham Hassan Bin
Abstract : The objective of this study was to authenticate the ethnobotanical claims of the Nepeta ruderalis Buch.-Ham. ( N. ruderalis ) extract in the traditional system of medicine. Crude extract was prepared via a simple maceration process. DPPH free radical scavenging and carrageenan-induced rat paw edema models were used to monitor antioxidant and anti-inflammatory responses of the N. ruderalis extract. Furthermore, it was tested for antiplatelet aggregation, cardioprotective, and calcium channel antagonistic activities via standard documented protocols. The N. ruderalis extract exhibited 80.82% antioxidant activity (I C 50 = 207.51 ± 4.36 μ g ) while the anti-inflammatory response was significant (p < 0.05 to p < 0.01 ) at 50 mg/kg (45.58%) and 100 mg/kg (60.90%) doses. Moreover, it was found to inhibit platelet aggregation (I C 50 = 1.06 and 0.91 mg/mL) and, in addition, to increase the force of contraction at the concentration of 3.0-10 mg/mL with a decrease in the heart rate on isolated paired atria (E C 50 = 11.78 mg / mL ). Relaxant activity was observed on the isolated rabbit jejunum (E C 50 = 0.96 mg / mL ) and trachea (E C 50 = 0.89 mg / mL ). However, in a cumulative way, an 80-millimolar potassium-induced contraction was evaluated (E C 50 = 1.31 mg / mL ). The N. ruderalis extract exhibited antioxidant, anti-inflammatory, platelet aggregating, cardiotonic, and calcium channel antagonistic activities, therefore proving scientifically its effectiveness in the traditional system of medicine.